2015
DOI: 10.1016/j.bios.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the aggregation problem: A new type of fluorescent ligand for ConA-based glucose sensing

Abstract: Competitive binding assays based on the lectin Concanavalin A (ConA) have displayed significant potential to serve in continuous glucose monitoring applications. However, to date, this type of fluorescent, affinity-based assay has yet to show the stable, glucose predictive capabilities that are required for such an application. This instability has been associated with the extensive crosslinking between traditionally-used fluorescent ligands (presenting multiple low-affinity moieties) and ConA (presenting mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…41,42 In this way, PEGylated-TRITC-ConA was formed with an average of ∼5 mPEG chains grafted per ConA monomer. 42 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 In this way, PEGylated-TRITC-ConA was formed with an average of ∼5 mPEG chains grafted per ConA monomer. 42 …”
Section: Methodsmentioning
confidence: 99%
“…31,39,40 Thus, we recently reported the use of a new type of competing ligand, aminopyrene trisulfonate mannotetraose (APTS-MT), which presents a single high-affinity trimannose moiety that utilizes the full binding site of ConA and thus avoids aggregation. 41 Additionally, we demonstrated that tethering of poly(ethylene glycol) (PEG) to ConA (i.e., PEGylation) improved ConA’s thermal stability and resistance to electrostatic binding. 42 Finally, we demonstrated improved FRET efficiency leading to enhanced sensitivity to changes in glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium chloride dihydrates (CaCl 2 ) was purchased from Mallinckrodt Chemical Inc (St. Louis, MO) and sodium chloride (NaCl) from J.T.Baker (Center Valley, PA). The competing ligand, amino-pyrene trisulfonate mannotetraose (APTS-MT) was synthesized with Dr. Vigh at Texas A&M University as previously described [9]. A 0.2 μm syringe filter from VWR (Radnor, PA) was used to filter all solutions before each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The FA assay was expected to maintain its response to glucose under thermal conditions as the addition of PEG chains should provide thermal stability of ConA. Also, the use of mannotetraos se should furth her prolong the assay's sensing capabilitie es as its been s shown to resul lt in a non-agg gregative assay [9]. …”
Section: Glucose Response (30 Days)mentioning
confidence: 99%
See 1 more Smart Citation